EFFICACY AND SAFETY OF HYPERBARIC OXYGEN THERAPY IN FISTULIZING CROHN'S DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (26th January 2023) - Dokmak, Amr; Sweigart, Benjamin; Orekondy, Nayantara; Jangi, Sushrut; Hamdeh, Shadi; Weinstock, Joel; Kochar, Gusmiran; Shen, Bo; Levy, Alexander
Abstract: BACKGROUND: Hyperbaric oxygen therapy (HBOT) delivers 100% oxygen in a pressurized chamber, increasing tissue oxygen levels and regulating inflammatory pathways. Despite significant expansion of the inflammatory bowel disease (IBD) therapeutics, there remains a significant gap in achieving fistula healing. Mounting evidence suggests that HBOT may be effective for IBD. Our systematic review and meta-analysis aimed to quantify the efficacy and safety of HBOT in fistulizing Crohn's disease (CD). METHODS: A systematic review was conducted using the EMBASE, Web of Science, Pubmed, and Cochrane Library databases according to PRISMA criteria. Study bias was assessed using the Cochrane handbook guidelines. Published articles and abstracts were included for analysis if they met study design criteria, evaluated HBOT efficacy in patients with fistulizing CD, and reported sufficient outcome data. Outcome data were considered sufficient when measured clinically, radiographically, and/or endoscopically. Randomized controlled trials, case-controlled studies, and case-series were included in the analysis. Our primary outcome of interest was overall clinical response with HBOT. Overall clinical response was defined as either clinical remission or partial response. Clinical remission was defined as closure of fistula and complete cessation of drainage. Partial response was defined as improvement in fistula drainage. RESULTS: Sixteen studies with 164 patients who underwent 5, 125 HBOT sessions were included in the analysis. For all fistula subtypes, the pooled overall clinical response was 87% (95% CI 0.70-0.95, I 2 =0) (Figure) and the pooled clinical remission was 59% (95% CI 0.35-0.80, I 2 =0). The overall clinical response was 89%, 84%, and 29% for perianal, enterocutaneous, and rectovaginal fistulas, respectively. (Table) On meta-regression, hours in the chamber and number of HBOT sessions were not found to correlate with a clinical response. The pooled number of adverse events was low at 51.7 per 10, 000 HBOT sessions for all fistula types (95% CI 16.8-159.3, I 2 =0). DISCUSSION: With a pooled overall clinical response rate of 87% and low adverse event rate, our review emphasizes the potential clinical benefit and safety of adjunctive HBOT in refractory cases of fistulizing CD. Rectovaginal fistulas were the fistula subtype least responsive to HBOT. Data limitations include study design heterogeneity and lack of control group presence. Randomized control trials are needed to substantiate the benefit of HBOT in fistulizing CD.